2005
DOI: 10.1044/1092-4388(2005/052)
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Related Acoustic Changes in Voiceless English Fricatives

Abstract: This investigation is a comprehensive acoustic study of 4 voiceless fricatives (/f theta s /) in English produced by adults and pre- and postpubescent children aged 6-14 years. Vowel duration, amplitude, and several different spectral measures (including spectral tilt and spectral moments) were examined. Of specific interest was the pattern of normal development of the acoustic properties of fricatives and the nature of sex-specific patterns of fricative articulation in prepubescent children. Little evidence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
57
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(70 citation statements)
references
References 25 publications
13
57
0
Order By: Relevance
“…This result supports the claim that the children with CIs produced /s/ with lower spectral peaks than the children with NH in the hearing age comparison because of differences in auditory perceptual abilities rather than differences in vocal tract size. The difference in the effect of age on spectral peaks of productions of /s/ and /$/ is consistent with results of Fox and Nissen (2005) who found that over a much larger age range, age explained more of the variability in spectral peak locations of /$/ than of /s/. Uchanski and Geers (2003) and Liker et al (2007) similarly noted that children with CIs produced reduced contrast between /s/ and /$/ due to the production of /s/ at lower frequencies.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…This result supports the claim that the children with CIs produced /s/ with lower spectral peaks than the children with NH in the hearing age comparison because of differences in auditory perceptual abilities rather than differences in vocal tract size. The difference in the effect of age on spectral peaks of productions of /s/ and /$/ is consistent with results of Fox and Nissen (2005) who found that over a much larger age range, age explained more of the variability in spectral peak locations of /$/ than of /s/. Uchanski and Geers (2003) and Liker et al (2007) similarly noted that children with CIs produced reduced contrast between /s/ and /$/ due to the production of /s/ at lower frequencies.…”
Section: Discussionsupporting
confidence: 78%
“…Since the children with CIs were older than the children with NH in the hearing age comparison, it was worth investigating whether the difference in /s/ production between the children with CIs and these children with NH was due to differences in vocal tract size. Previous studies have found that children produce fricatives at higher frequencies than adults (Nittrouer, 1995;Fox and Nissen, 2005). This is consistent with the fact that children have smaller vocal tracts than adults, and therefore their fricative productions resonate at higher frequencies.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Therefore, the M1 value of /s/ is expected to be higher than that of /$/ because of the shorter front resonating cavity in /s/. This prediction has been confirmed robustly in many acoustic studies of English fricatives (Forrest et al, 1988;Jongman, et al, 2000;Nissen and Fox, 2005;Nittrouer, 1995;Shadle and Mair, 1996;Fox and Nissen, 2005).…”
Section: Introduction a Overviewmentioning
confidence: 58%
“…Miccio et al (1996) found all four moments are effective in describing the /s/-/$/ distinctions produced by normal developing children. Similarly, Nissen and Fox (2005) and Fox and Nissen (2005) also utilized spectral moments analysis to describe fricative productions by children, adolescents, and adults. They found that all four moments are useful in describing children's /s/ and /$/ distinctions and the two sounds are better distinguished acoustically as children's ages increase.…”
Section: Introduction a Overviewmentioning
confidence: 99%